DETERMINANTS OF HOUSEHOLD FOOD SECURITY: A COMPARATIVE ANALYSIS OF EASTERN AND WESTERN INDONESIA - Wiranthi, Puspi Eko; Suwarsinah, Heny Kuswanti; Adhi, Andriyono Kilat (Indonesian Journal of Agricultural Science, 2014)
Indonesian Food Security Council in 2009 issued a Food Security and Vulnerability Atlas (FSVA) which stated that there were 100 districts in Indonesia which were most vulnerable to food insecurity and 79% of which were located in eastern region. By using Susenas regular data in 2008, this study aimed to analyze determinants of household food security in eastern compared to western region. The ordered logistic regression model was employed to investigate the determinants of household food security. The result showed that most of households in Indonesia were vulnerable to food insecurity (41.76%). The percentage in eastern region (48.56%) was higher than that in western region (41.76%). Increase in expenditure equivalent, age and education level of household head, female household head, small household size, household headâs occupation in non-agriculture and urban household would increase the probability of a household to become food secure in both regions. The difference was in the factor of access to electricity in eastern and access to safe drinking water and loan in western region. Policies which aim to increase education, credit access, and intensive family planning have big roles in improving household food security.